2018
DOI: 10.1371/journal.pone.0197376
|View full text |Cite
|
Sign up to set email alerts
|

Causes and predictors of mortality in Asian Indians with and without diabetes–10 year follow-up of the Chennai Urban Rural Epidemiology Study (CURES - 150)

Abstract: BackgroundThe incidence and prevalence of diabetes is increasing worldwide and it is the fifth leading cause of mortality accounting for over 3.8 million deaths annually. Despite the enormity of the diabetes-related health burdens, very few studies have evaluated the factors associated with mortality among people with diabetes in India. We sought to study the causes and predictors of mortality among urban Asian Indians with and without diabetes.Methods and findingsOf 2273 adults (27,850 person-years of follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…Over the working lifespan of the diabetes cohort, higher all-cause mortality risk in those with diabetes resulted in a 5.5% reduction in years of life lived and was similar in men and women. This is consistent with the previous study conducted in India 21 but is contrary to the findings of a study conducted in China, which showed a higher mortality risk among working age Chinese men than women. 29 The relative impact of diabetes on years of life lost was higher among Bangladeshi younger people due to their longer working lifespan.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Over the working lifespan of the diabetes cohort, higher all-cause mortality risk in those with diabetes resulted in a 5.5% reduction in years of life lived and was similar in men and women. This is consistent with the previous study conducted in India 21 but is contrary to the findings of a study conducted in China, which showed a higher mortality risk among working age Chinese men than women. 29 The relative impact of diabetes on years of life lost was higher among Bangladeshi younger people due to their longer working lifespan.…”
Section: Discussionsupporting
confidence: 88%
“…20 Since there were no mortality rates in Bangladesh, age and sex-specific mortality data for 2017 were extrapolated from the Chennai Urban Rural Epidemiology Study-150. 21 These were attributed to those with and without diabetes based on age and sex-specific diabetes prevalence and the relative risk of all-cause mortality associated with diabetes in Bangladeshi populations. Based on an assumption that the mortality rate for a 5 years age group applied to people in the midpoint of that age band, mortality rates for age in single years were derived using exponential functions (online supplimentary EMS table 2).…”
Section: Population and Mortality Ratesmentioning
confidence: 99%
“…9 However, only a few studies have been conducted to describe the patterns and predictors of mortality in South Asian populations and even fewer are based on population-based cohorts. 10 Well organised and functioning vital registration systems provide high quality and timely mortality data that are of great value for epidemiological purposes. At present, the rate of death registration in Sri Lanka exceeds 99% and on registration, a death certificate is issued.…”
Section: Open Accessmentioning
confidence: 99%
“…2 The high prevalence of ASCVD in persons with diabetes is well documented in many populations of the world. 3 Individuals with diabetes have higher atheroma volume, more atherosclerotic plaque and much narrower coronary lumen than do nondiabetics. 4 This makes them at great risk for a much worse myocardial infarction and occurrence of silent myocardial infarction; however, the concept of diabetes as a risk equivalent for established coronary artery disease is still not universally accepted.…”
Section: Clinical Summarymentioning
confidence: 99%